1,10-Phenanthroline as an Analytical Reagent for the Estimation of Cefepime and Repaglinide - Gowri Sankar, D.; Vamsi Krishna, M.; Kumar, D.V.S.P.; Latha, P.V.M. (Asian Journal of Chemistry, 2016)
A simple and sensitive spectrophotometric method has been developed for the estimation of cefepime (CFM) and repaglinide (RGP) in pure as well as in pharmaceutical formulations. This method is based on the oxidation of drug with ferric chloride followed by complexation with 1,10-phenanthroline (1,10-PTL) to form a blood red coloured chromogen exhibiting maximum absorbance at 520 nm (for CM) or 515 nm (for RPG). Beer’s law is obeyed in the concentration range of 1–7.5 μg/mL for CFM and 2.5–15 μg/mL for RPG. The method was extended to pharmaceutical formulations. There was no interference from any common pharmaceutical excipients and diluents.